2017
DOI: 10.1002/arch.21383
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of candidate odorant‐binding proteins and chemosensory proteins in the tea geometrid Ectropis obliqua Prout (Lepidoptera: Geometridae)

Abstract: Insects rely heavily on their sophisticated chemosensory systems to locate host plants and find conspecific mates. Although the molecular mechanisms of odorant recognition in many Lepidoptera species have been well explored, limited information has been reported on the geometrid moth Ectropis obliqua Prout, an economically important pest of tea plants. In the current study, we first attempted to identify and characterize the putative olfactory carrier proteins, including odorant-binding proteins (OBPs) and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 74 publications
(96 reference statements)
2
21
0
Order By: Relevance
“…We consider that the OSNs population coding accounts for OR function and expression. However, to date, only a few studies of the expression of relevant candidate olfactory genes have been carried out in E. grisescens and E. obliqua (Li et al, ; Sun et al, ). Further comparative studies of function, response profiles, and expression patterns of ORs between the two species are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that the OSNs population coding accounts for OR function and expression. However, to date, only a few studies of the expression of relevant candidate olfactory genes have been carried out in E. grisescens and E. obliqua (Li et al, ; Sun et al, ). Further comparative studies of function, response profiles, and expression patterns of ORs between the two species are required.…”
Section: Discussionmentioning
confidence: 99%
“…For E. obliqua , the components are Z3,epo6,Z9–18:H, Z3,Z6,Z9–18:H, and (Z,Z)‐3,9‐ cis ‐6,7‐epoxy‐nonadecadiene (Z3,epo6,Z9–19:H) at a ratio of 4:2:4 (Luo, Li, Cai, Bian, & Chen, ). Several studies have focused on volatile analytical chemistry, behavior, antennal morphology, and molecular biology of olfactory receptors (ORs) and genetic analysis of candidate olfactory binding proteins of the two species (Li et al, ; Luo et al, ; Ma, Bian, et al, ; Ma, Xiao, et al, ; Sun et al, ; Zhang et al, ), but no experiments have investigated sensillum physiology.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-tissue expression pattern of CSPs indicate they may also have other functions, apart from chemo sensation (Tegoni et al, 2004). In fact, with the development of genome and transcriptome sequencing, recent studies have demonstrated that CSPs do contribute to other physiological processes Kang, 2016;Zhang et al, 2017;Ting et al, 2018;Zeng et al, 2018). As carrier proteins, CSPs bind with small molecules, for instance nutrients, toxic compounds, hormones and semiochemicals, (Pelosi et al, 2017).…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
“…The reference genes Eoblβ-actin (Ma et al, 2016) and EoblGAPDH (Sun, Mao et al, 2017) were previously demonstrated to be suitable for estimating relative expression levels of E. obliqua olfactory genes; therefore, we selected them as housekeeping genes to normalize EoblSNMP1-2 gene expression and to correct for sample-to-sample variation. Negative controls were nontemplate reactions (sterilized H 2 O instead of cDNA).…”
Section: Insect and Tissue Collectionmentioning
confidence: 99%
“…Negative controls were nontemplate reactions (sterilized H 2 O instead of cDNA). The reference genes Eoblβ-actin (Ma et al, 2016) and EoblGAPDH (Sun, Mao et al, 2017) were previously demonstrated to be suitable for estimating relative expression levels of E. obliqua olfactory genes; therefore, we selected them as housekeeping genes to normalize EoblSNMP1-2 gene expression and to correct for sample-to-sample variation. The amplification efficiencies of the target and reference genes were assessed by examining the variation of ΔCt (Ct target -Ct reference) with template gradient dilution (Livak & Schmittgen, 2001).…”
Section: Insect and Tissue Collectionmentioning
confidence: 99%